FAKTOR-FAKTOR PENENTU PERKEMBANGAN EMOSIONAL PADA ANAK: Factors Determining Emotional Development In Children - Dian Furwasyih; Yulia Arifin; Gina Muthia (LPPM - STIKES Pemkab Jombang, 2025)
Emotional development is a crucial aspect of child growth that determines long-term mental health, social competence, and academic achievement. Screen exposure and nutritional status are key modifiable factors that may influence children’s socio-emotional outcomes, yet limited evidence exists regarding their combined effects in urban Indonesian settings. A cross-sectional study was conducted in Padang City, Indonesia, from January to July 2025, involving 56 children aged 5–10 years. Emotional development was assessed using a validated questionnaire (Cronbach’s alpha = 0.87). Screen exposure was categorized as ?2 hours/day or >2 hours/day based on caregiver reports. Height-for-age and weight-for-age were measured using WHO Anthro software. Data were analyzed with Chi-square tests and multivariate logistic regression to identify predictors of emotional development. Among the participants, 67.9% had screen exposure >2 hours/day, 26.8% had abnormal height-for-age, and 32.1% had abnormal weight-for-age. Overall, 30.4% demonstrated poor emotional development. Multivariate analysis showed that screen exposure >2 hours/day was significantly associated with poor emotional development (AOR = 4.84; 95% CI: 1.37–17.14; p = 0.014). Abnormal height-for-age (AOR = 3.76; 95% CI: 1.04–13.53; p = 0.043) and abnormal weight-for-age (AOR = 3.42; 95% CI: 1.02–11.42; p = 0.048) were also independent predictors. Sex was not significantly associated. Excessive screen exposure and abnormal nutritional status were significant determinants of poor emotional development among children in Padang City. Interventions should prioritize parental regulation of screen use, promotion of interactive play, and nutritional improvement strategies. Collaborative efforts between families, schools, health professionals, and policymakers are essential to enhance children’s socio-emotional well-being.